Management of sports budgeting on maintenance of facilities in Kwara State Sports Council, Nigeria - Falaye Elijah Kayode; Ajadi Memunat Tunrayo (Indonesian Journal of Sport Management, 2022)
This study examined the Management of Sports Budgeting on Maintenance of Facilities in Kwara State Sports Council. Descriptive research design of survey type was used for this study. The population for the study comprised of all 110 staff in Kwara Sports Council. Multistage sampling techniques were used for this study. Stratified sampling techniques was used to group the departments in the study area. While purposive sampling technique was used to select all 110 respondents. Researcher structured questionnaire was used as instrument for the study.The instrument were validated by 3 lecturers in Department of Human Kinetics Education, University of Ilorin and the reliability level of the instrument was establish through test re-test method using Pearson Product Moment (PPMC). A correlation co-efficient of 0.65 was obtained. The instrument were administered by the researchers and three trained research assistants. The data collected were analysed using inferential statistics of chi-square at 0.05 alpha level. The result revealed that bureaucratic process, zero-based budget and bottom-up budget have significant impact on maintenance of sports facilities. The study recommends that bureaucratic process should not be used during the selection of sports budgeting so as to enhance maintenance of sports facilities. Also sports budgeting should be prepared based on zero budget that would enhance effective management of sports facilities.